Is the sexual sensation seeking scale a reliable instrument? Addressing multiple factor structures in a Colombian sample - Romero, D.; Rodrigues, D. L.; Mebarak, M.; Tovar-Castro, J. C.; Millán, A. (Psychology and Sexuality, 2023)
The sexual sensation seeking scale (SSSS) is a widely used instrument to measure individuals’ tendency to seek an optimal level of sexual arousal and novel sexual experiences. However, psychometric studies have suggested different factor structures for this instrument, which may lead to a biased assessment of the subdimensions of sexual sensation seeking. The present study (N = 812) aimed to identify the best factorial model of the SSSS by comparing the model suggested by previous research. Results from Exploratory and Confirmatory Factor Analyses showed that none of the models tested have sufficient goodness-of-fit to support the internal validity of the instrument. Thus, this study highlights the limitations of the SSSS in assessing sexual sensation seeking and proposes psychometric alternatives that should be considered by researchers to achieve a reliable measure of sexual sensation seeking.